Patient Referral Systems: key processes of health services management - ถ่างกระโทก ปราโมทย์ (Journal of Medicine and Health Sciences, 2018)
Patient referral systems play an increasingly important role in the health services systems. Patient referral systems should aim to helps and ensure people receive the best possible care, comprehensive, equity and continuing care. This article presented core process of a patient referral system, as follow: 1) initiating facility 2) receiving facility 3) referral practicalities and support process of a patient referral system, as follow: 1) health system issues 2) supervision and capacity building 3) continuous quality improvement. Analyze the situation of patient referral system, was collected from Ministry of Public Health and Bangkok Metropolitan Administration documents. This article recommendations for the development of an effective patient referral system.